Tinjauan Literatur (2021-2025): Penerapan Deep Learning dalam Peningkatan Penalaran Kritis Siswa: Literature Review (2021-2025): Application of Deep Learning in Improving Students' Critical Reasoning - Dian Ermayani Sigalingging; Mintarsih Arbarini; Bambang Subali; Ellianawati Ellianawati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The rapid development of artificial intelligence (AI) technology since 2021 has opened up new opportunities in education, particularly in the application of deep learning approaches as adaptive learning strategies. This approach enables a more personalized, interactive, and data-driven learning process, potentially enhancing higher-order thinking skills, particularly students' critical reasoning abilities. Critical reasoning is a crucial competency in 21st-century learning because it helps students analyze information, evaluate arguments, and make rational and reflective decisions. This literature review aims to identify, analyze, and evaluate research published from 2021 to 2025 that addresses the effectiveness of deep learning applications in learning-oriented approaches to improving critical thinking skills. The study used a systematic literature review approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, which includes the stages of article identification, screening, eligibility, and inclusion. The literature search process was conducted using Publish or Perish through the Scopus and Google Scholar databases. Of the 120 articles found, 10 articles that met the inclusion criteria were selected for further analysis. The analysis was conducted using a content analysis and bibliometric approach with the help of VOSviewer software to map keyword relationships and research trends. The review results indicate that the application of AI-based deep learning has the potential to improve students' critical reasoning by fostering learning that emphasizes personalization, in-depth concept exploration, and the strengthening of reflective and analytical thinking.